Paraneoplastic myopathy secondary to cholangiocarcinoma: a case report - Quintero Fuentes, Carolina; Ayala Vergara, Camila; Avello Medrano, Marian (Revista Chilena de Estudiantes de Medicina, 2024)
Introduction: Idiopathic inflammatory myopathies (IIM) are a rare group of diseases that mainly manifest with muscle involvement. Their association with neoplasms has been described, especially with gastrointestinal adenocarcinoma, lung and breast cancer. Cholangiocarcinoma (CCA) is a rare neoplasm originating from the epithelial cells of the bile ducts, whose primary manifestation is cholestatic syndrome. Case presentation: A 74-year-old female has a one-month history of acholia, jaundice, generalized pruritus, significant weight loss, and proximal muscle weakness progressing to prostration. Laboratory findings show a cholestatic pattern with direct hyperbilirubinemia of 16.9 mg/dL; Computed Tomography of the chest, abdomen, and pelvis reveals intrahepatic bile duct dilation and thickening of the extrahepatic bile duct wall; Cholangioresonance describes a suspicious lesion of CCA Bismuth IV. Given the patient’s functional status and the level of bile duct involvement, palliative management is initially determined. Evaluated by Rheumatology due to suspicion of paraneoplastic IIM, further studies include creatine kinase 1257 mg/dL, electromyography showing a myopathic pattern, and a negative myositis panel, ruling out an autoimmune origin. Systemic corticosteroids are started, achieving complete mobility recovery. Due to a favorable evolution, an endobiliary biopsy is performed, confirming cholangiocarcinoma and reaffirming the association between myopathy and neoplasm. Discussion: The importance of suspecting a paraneoplastic myopathy in patients with active neoplasms and muscle weakness lies in the possibility of optimizing functional status and allowing for broader neoplastic management to improve patients’ quality of life.